Settlement monitoring of georehabilitation solution at bridge and culvert approaches using polyurethane foam injection system - Mohamed Jais, Ismacahyadi Bagus; Abdul Rahman, Abdul Samad; Mohamad Abas, Fairul Zahri; Zainuddin, Nurul Eilmy; Md Ali, Mohamed Azizi (Faculty of Civil Engineering, 2026)
Differential settlement at transition approaches has caused major problems to road users whereby the kink at the approach section could affect the riding ability and discomfort. The issues relating to differential settlement is due to high dynamic impact from heavy traffic loads, consolidation settlement of the foundation soil, poor compaction and migration of the earth fill underneath the voids of the piled embankment or bridge abutment created from global settlement of the surrounding area. The proposed solution mostly resorts to the reconstruction of the approaches, thereby requires excavation and construction of transition or approach slabs. In this paper, an alternative solution using polyurethane (PU) foam injection system was introduced to reduce the effect of differential settlement at the approach bridges and culverts, thus provide minimal disruption to traffic users and operations. The objectives of the proposed georehabilitation solution are i) to reduce the effect of soil migration and settlement underneath the transition section; and ii) to stabilize the ground by increasing the bearing resistance without increasing the existing overburden pressure to the foundation soil. Settlement monitoring was conducted to ensure that the solution performs to the required specification. This paper will provide results for two (2) locations at FT005, Kuala Selangor Federal Road, specifically, the Kuala Selangor bridge approach and the Sungai Gulang-Gulang culvert approach. The results showed that there is significant reduction in the differential settlement of the approach sections, hence the need to resurface or regulate the pavement for routine maintenance is needed.